Penetration of doxycycline into cerebrospinal fluid in patients treated for suspected Lyme neuroborreliosis. - Dotevall, L (1989)
Twelve patients were treated orally with 100 mg of doxycycline twice a day (b.i.d.) and 10 patients were treated with 200 mg b.i.d. for suspected tick-borne neuroborreliosis (Lyme borreliosis). At 5 to 8 days after the start of therapy, the mean concentrations in serum were 4.7 micrograms/ml for the doxycycline dose of 100 mg b.i.d. and 7.5 micrograms/ml for 200 mg b.i.d., 2 to 3 h after the last drug administration. The corresponding levels for cerebrospinal fluid were 0.6 and 1.1 micrograms/ml. Since a doxycycline concentration in cerebrospinal fluid above the estimated MIC for Borrelia burgdorferi (0.6 to 0.7 microgram/ml) is wanted in patients treated for severe neuroborreliosis, the higher dose is preferable.